2016
DOI: 10.1097/bor.0000000000000310
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of systemic lupus erythematosus and Sjögren's syndrome: an update

Abstract: SLE and Sjögren's syndrome are two closely related systemic autoimmune diseases that share multiple clinical and molecular aspects, including a significant number of susceptibility genes. Several genome-wide association studies were recently published in different populations that provide a better picture of their molecular mechanisms. It is becoming clear that their genetic architecture is quite well established, but more information is required on expression quantitative trait loci, epigenetic genome-wide an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 92 publications
2
33
0
5
Order By: Relevance
“…As expected from the genetic similarities between SLE and SS (Teruel and Alarcon-Riquelme, 2016), we confirmed that T cells from patients with SS, like SLE, were poorer responders to allogenic non-T cells than T cells from healthy donors (Russell et al., 1983). Furthermore, we could evaluate M3R-reactive CD4+ T cells, which are thought to be one of the pathogenic T cells for SS.…”
Section: Discussionsupporting
confidence: 88%
“…As expected from the genetic similarities between SLE and SS (Teruel and Alarcon-Riquelme, 2016), we confirmed that T cells from patients with SS, like SLE, were poorer responders to allogenic non-T cells than T cells from healthy donors (Russell et al., 1983). Furthermore, we could evaluate M3R-reactive CD4+ T cells, which are thought to be one of the pathogenic T cells for SS.…”
Section: Discussionsupporting
confidence: 88%
“…A possible explanation for the fact that NETs lead to the activation of self-reactive B cells that produce Abs against NETs in LE patients but not in healthy donors is that LE patients have a genetically determined tendency for increased B cell activation. In fact, susceptibility genes involving B cell function and signaling, including BANK, BLK, and LYN, have been found in LE patients (20). Other susceptibility genes include genes involved in type I IFN signaling, such as TLR7, IRF5, TYK2, STAT4, IFIH1, TREX, and STING (20), which may decrease the threshold for B cell activation in LE.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, susceptibility genes involving B cell function and signaling, including BANK, BLK, and LYN, have been found in LE patients (20). Other susceptibility genes include genes involved in type I IFN signaling, such as TLR7, IRF5, TYK2, STAT4, IFIH1, TREX, and STING (20), which may decrease the threshold for B cell activation in LE. As a consequence, the break of B cell tolerance leads to the production of anti-NET Abs that further promote NET formation (5) and decrease NET degradation in LE (13)(14)(15), providing a feedback loop that sustains the inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…There are more than 15 robust susceptibility loci identified for SS and many of these are shared with SLE [33]. Similar to SLE, patients with SS display increased expression of type I and type II IFN-regulated genes in both salivary tissue and peripheral blood [19, 30, 3438].…”
Section: Genetic Studies In Pss Patients Identify Polymorphisms Inmentioning
confidence: 99%